Remote Magnetic Field Sensor Based on Intracavity Absorption of Evanescent Field - Jia Shi; Yuye Wang; Degang Xu; Genghua Su; Haiwei Zhang; Jiachen Feng; Chao Yan; Shijie Fu; Jianquan Yao (IEEE Photonics Journal)
In this paper, a remote magnetic field sensor based on intracavity absorption of evanescent field is experimentally demonstrated. A single-mode–no-core–single-mode (SNCS) fiber coated with magnetic fluid (MF) is inserted into a fiber ring laser through a circulator and a 3-dB coupler, and it works as the filter and sensing head simultaneously. As the light oscillates in the cavity of the fiber ring laser, intracavity absorption of the evanescent field will be induced in the interface of the no-core fiber and MF. We obtain a magnetic field sensor with a narrow 3-dB bandwidth that is less than 0.05 nm, a high signal-to-noise ratio ∼40 dB, and magnetic sensitivity of 52.1 pm/mT and −0.3679 dBm/mT. Moreover, experiments show that it is convenient to achieve remote sensing by selecting different lengths of the transmission optical fiber connecting the circulator and 3-dB coupler, which has a slight impact on the sensitivity.